Biometal Dyshomeostasis in Olfactory Mucosa of Alzheimer's Disease Patients - Lampinen, Riikka; Górová, Veronika; Avesani, Simone; Liddell, Jeffrey R; Penttilä, Elina; Závodná, Táňa; Krejčík, Zdeněk; Lehtola, Juha-Matti; Saari, Toni; Kalapudas, Juho; Hannonen, Sanna; Löppönen, Heikki; et al. (International journal of molecular sciences, 2022)
Olfactory function, orchestrated by the cells of the olfactory mucosa at the rooftop of the nasal cavity, is disturbed early in the pathogenesis of Alzheimer's disease (AD). Biometals including zinc and calcium are known to be important for sense of smell and to be altered in the brains of AD patients. Little is known about elemental homeostasis in the AD patient olfactory mucosa. Here we aimed to assess whether the disease-related alterations to biometal homeostasis observed in the brain are also reflected in the olfactory mucosa. We applied RNA sequencing to discover gene expression changes related to metals in olfactory mucosal cells of cognitively healthy controls, individuals with mild cognitive impairment and AD patients, and performed analysis of the elemental content to determine metal levels. Results demonstrate that the levels of zinc, calcium and sodium are increased in the AD olfactory mucosa concomitantly with alterations to 17 genes related to metal-ion binding or metal-related function of the protein product. A significant elevation in alpha-2-macroglobulin, a known metal-binding biomarker correlated with brain disease burden, was observed on the gene and protein levels in the olfactory mucosa cells of AD patients. These data demonstrate that the olfactory mucosa cells derived from AD patients recapitulate certain impairments of biometal homeostasis observed in the brains of patients.
Keywords: Calcium; Humans; vápník; zinc; stopové prvky; Zinc; lidé; Alzheimer Disease; Alzheimer’s disease; Alzheimerova nemoc; zinek; alpha-2-macroglobulin; Olfactory Mucosa; olfactory mucosa cells; calcium; Trace Elements; chelátory; olfactory dysfunction; biometals; sodium; Chelating Agents; čichová sliznice